2016
DOI: 10.1108/ijphm-09-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

“Infecting” those we care about: social network effects on body image

Abstract: Purpose This paper aims to explore the forces at work that negatively influence the self-image perceptions of young women, causing them to strive for an “ultra-thin” ideal. Design/methodology/approach Focus groups explore why and how perceived self-image influences young women’s body and perceptions and, consequently, health. Thematic qualitative analysis explores the realm of information and emotions involved with the thin-ideal. Findings Social contagion theory emerged with a significant impact caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…A greater predisposition to engage in physical comparisons mediated relationships between image‐related exposure and body dissatisfaction, drive for thinness, increased dieting . This finding was consistent across all SM platforms, cohorts, genders and locations . Comparisons made with female celebrities, had higher associations to body dissatisfaction followed by comparisons with close friends and distant peers …”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…A greater predisposition to engage in physical comparisons mediated relationships between image‐related exposure and body dissatisfaction, drive for thinness, increased dieting . This finding was consistent across all SM platforms, cohorts, genders and locations . Comparisons made with female celebrities, had higher associations to body dissatisfaction followed by comparisons with close friends and distant peers …”
Section: Resultssupporting
confidence: 56%
“…A variety of tools to measure BI and eating behaviour were used, with little overlap between the studies (Appendix S3). However, the Eating Disorder Examination Questionnaire (EDEQ), Eating Disorder Inventory (EDI), Objectified Body Consciousness (OBC‐Y) and Physical Appearance Comparison Scale (PACS) were the most frequently utilised measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent medical research, albeit incipiently, have indicated a positive association between the effects of social media use among young female university students and the development of the Mirror Syndrome, i.e., a mental disorder involving individuals' distorted perception about their physical appearance. According to Grover et al (2016), young women try to be in line with the idea of beauty promoted by social media influencers and, while doing so, naturalize the external psycho-emotional conditions to achieve a goal (e.g., having shiny white teeth; meeting certain body configurations; wearing a particular clothing size, manicure designs, amongst others) set by these social media influencers. This can, at times, end up developing several mental, emotional, and physical conditions such as depression, Body Dysmorphic Disorder (BDD), anxiety, social isolation, or loss of self-esteem.…”
Section: Online Social Networkmentioning
confidence: 99%